(untitled) (Texas Journal of Medical Science, 2025)
Preparation for surgical intervention includes extensive laboratory and clinical examination of the patient. Its purpose is to identify any pathologies (chronic and acute diseases), as well as to identify any risks that may cause serious complications during the operation. Tests also help to make the most accurate diagnosis and find out the exact state of the disease.